Mechanisms of Arsenic Hyperaccumulation in Pteris vittata. Uptake Kinetics, Interactions with Phosphate, and Arsenic Speciation - Wang, Junru (American Society of Plant Biologists, 2002)
The mechanisms of arsenic (As) hyperaccumulation in Pteris vittata, the first identified As hyperaccumulator, are unknown. We investigated the interactions of arsenate and phosphate on the uptake and distribution of As and phosphorus (P), and As speciation in P. vittata. In an 18-d hydroponic experiment with varying concentrations of arsenate and phosphate, P. vittata accumulated As in the fronds up to 27,000 mg As kg(−1) dry weight, and the frond As to root As concentration ratio varied between 1.3 and 6.7. Increasing phosphate supply decreased As uptake markedly, with the effect being greater on root As concentration than on shoot As concentration. Increasing arsenate supply decreased the P concentration in the roots, but not in the fronds. Presence of phosphate in the uptake solution decreased arsenate influx markedly, whereas P starvation for 8 d increased the maximum net influx by 2.5-fold. The rate of arsenite uptake was 10% of that for arsenate in the absence of phosphate. Neither P starvation nor the presence of phosphate affected arsenite uptake. Within 8 h, 50% to 78% of the As taken up was distributed to the fronds, with a higher translocation efficiency for arsenite than for arsenate. In fronds, 49% to 94% of the As was extracted with a phosphate buffer (pH 5.6). Speciation analysis using high-performance liquid chromatography-inductively coupled plasma mass spectroscopy showed that >85% of the extracted As was in the form of arsenite, and the remaining mostly as arsenate. We conclude that arsenate is taken up by P. vittata via the phosphate transporters, reduced to arsenite, and sequestered in the fronds primarily as As(III).